Massive hyperphosphatemia in a patient with neuronal intestinal dysplasia after bowel preparation with oral sodium phosphate - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
Oral sodium phosphate-based laxatives are frequently used for bowel preparation or relief of constipation in some countries. However, these agents are not without risk. Small and clinical insignificant increments on serum phosphorus levels are observed in almost all individuals after use of oral sodium phosphate. Some patients are prone to severe hyperphosphatemia such as elders, those with chronic or acute renal disease and those with poor bowel motility. Severe hyperphosphatemia accompanied with hypocalcemia may be life-threatening in these patients. We present an 18-year-old woman with neuronal intestinal dysplasia who developed symptomatic and severe hyperphosphatemia after bowel preparation with oral sodium phosphate enema. Urgent hemodialysis was performed two times for severe hyperphosphatemia.
Keywords: Extreme hyperphosphatemia; neuronal intestinal dysplasia; sodium phosphate; RENAL-FAILURE; COLONOSCOPY